International struggle for new human rights - Bob, Clifford, 1958- (Philadelphia : University of Pennsylvania Press, 2009)
"Why are certain global problems recognized as human rights issues while others are not? How do local activists transform long-standing problems into universal rights claims? When and why do human rights groups, governments, and international organizations endorse new rights? The International Struggle for New Human Rights is the first book to address these issues." "Focusing on activists who advance new rights, the book introduces a framework for understanding critical strategies and conflicts involved in the struggle to persuade the human rights movement to move beyond traditional problems and embrace pressing new ones." "Essays in the volume consider rights activism by such groups as the south Asian Dalits, sexual minorities, and children of wartime rape victims, while others explore new rights issues such as health rights, economic rights, and the right to water. Examining both the successes and failures of such campaigns, The International Struggle for New Human Rights will be a key resource not only for scholars but also for those on the front lines of human rights work."--Jacket.
Introduction : fighting for new rights / Clifford Bob -- Orphaned again? Children born of wartime rape as a non-issue for the human rights movement / R. Charli Carpenter -- "Dalit rights are human rights" : untouchables, NGOs, and the Indian state / Clifford Bob -- Applying the gatekeeper model of human rights activism : the U.S.-based movement for LGBT rights / Julie Mertus -- From resistance to receptivity : transforming the HIV/AIDS crisis into a human rights issue / Jeremy Youde -- Disability rights and the human rights mainstream : reluctant gate-crashers? / Janet E. Lord -- New rights for private wrongs : female genital mutilation and global framing dialogues / Madeline Baer and Alison Brysk -- Economic rights and extreme poverty : moving toward subsistence / Daniel Chong -- Local claims, international standards, and the human right to water / Paul J. Nelson.
Includes bibliographical references (p. [141]-177) and index.
Keywords: Human rights -- Case studies; Droits de l'homme -- études de cas